The relationship between online tools for e-learning and student satisfaction - Khairul, Filda Nur Khalis; Sairudin, Siti Nurain Syahirah; Ibrahim, Muhamad Shamsul (The Asian Journal of Professional & Business Studies, 2021)
The advancement in communication technology impacts many sectors, including education. Many tertiary institutions have implemented e-learning in their teaching and learning process in the education sector. E-learning is becoming a new norm in teaching and learning, especially during the pandemic. Besides, e-learning has also become one of the marketing tools for educational institution to attract working adults to pursue their studies at a higher level. E-learning is perceived as the best alternative to help working adults get better education levels for a job promotion. In addition, e-learning is preferred because it is convenient and flexible, easy to update subject content, and increases student skill and knowledge using technology. Furthermore, the fees are cheaper than the physical class. The study conducted an online survey of 343 respondents to measure the research instrument reliability before the actual data collection. The study used a quota sampling approach to collect the response. The research instrument is considered reliable because the reliability analysis indicated more than 0.8. The pre-analysis indicated that the studied online tools, namely email, social network, and web portal, showed moderately related student satisfaction. The study indicates that KUPTM students are leaning toward using social networks as a preferable e-learning platform over web portal and e-mail